A new species of Myrcia sect. Aulomyrcia (Myrtaceae) from the restingas of Bahia, Brazil - Marinho, Lucas C.; Lucas, Eve (Phytotaxa, 2016)
The new species Myrcia raminfinita is described and illustrated; diagnostic characters such as large solitary bracts subtending auxotelic inflorescences and striking bracts covered in silky silver hairs are contrasted to closely related M. micropetala. Both species belong to Myrcia section Aulomyrcia and share persistent bracts, bilocular ovaries and covered by the indumentum peduncles, hypanthia and calyx lobes. The species occurs in Southern Bahian restinga (Brazil).